Faktor-Faktor yang Mempengaruhi Pemasaran Jagung oleh Petani di Kabupaten Boalemo - Machieu, Siti Rahmatia; Hippy, Mohammad Zubair (Program Studi Agribisnis Faperta Universitas Muhammadiyah Bengkulu, 2025)
The study aims to determine the effect of production capacity, location, capital, transport and marketing management partially and simultaneously on the effectiveness of maize marketing by farmers in Boalemo District. This research is quantitative research. The data source in this study is secondary data in the form of primary data from distributing questionnaires to corn farmers in Gorontalo Regency with a sample size of 77 farmers. The data analysis technique used is multiple regression analysis. The results of this study show that (1) Partially, farm capital, transport, and marketing management have a positive and significant effect on the effectiveness of maize marketing in Boalemo District. Meanwhile, production capacity and farm location have a positive but insignificant effect on the effectiveness of maize marketing in Boalemo District. All independent variables have positive coefficients, indicating that the more optimal these factors are, the more effective maize marketing in Boalemo district will be. (2) Simultaneously, production capacity, farm capital, farm location, transport, marketing management and distance together affect the effectiveness of maize marketing in Boalemo District. the adjusted R2 coefficient of determination is 0.627. This value means that 62.7% of the effectiveness of maize marketing in Boalemo Regency, Gorontalo Province can be explained by production capacity, farm capital, farm location, transport, and marketing management in Boalemo Regency, Gorontalo Province. While 37.3% is explained by other factors outside the model. Other factors outside the model are distribution channels and government policies. Keywords: Marketing; Maize; Farmers; Agribusiness; Boalemo